Cytotoxicity, genotoxicity and antimutagenicity of hexane extracts of Agaricus blazei determined in vitro by the comet assay and CHO/HGPRT gene mutation assay - Machado, M. P.; Rodrigues, E.; Terezan, A. P.; Ribeiro, U. R.; Mantovani, M. S. (Elsevier B.V., 2005)
Agaricus blazei Murrill ss. Heinem, known as the sun mushroom or himematsutake, is a basidiomycete native to Brazil, which is popular for its medicinal properties. The aim of this study was to test hexane extracts (one fraction and its four sub-fractions) of A. blazei for bioactivity in cultured mammalian cells (CHO-K1). The comet assay, the colony forming assay (CFA) and CHO/HGPRT gene mutation assay were used respectively to determine genotoxicity, cytotoxicity and antimutagenicity of these extracts at different concentrations. The cells were incubated in culture medium and treated for 3 h according to the standard protocol for each assay. The DNA damage-inducing agent ethylmethane sulfonate (EMS) was utilized as the positive control and also in combination with extracts to test for a protective effect. Statistical analysis of the data was performed using analysis of variance (ANOVA) and Tukey's test. A relationship between cytotoxicity and genotoxicity could be established and two extracts EH6B and EH6D showed a protective tendency, while the others did not, with the primary extract EH6 causing the most substantial damage to genetic material. These findings warrant more in-depth studies of the active principles of this mushroom. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Agaricus blazei; CHO-K1 cells; comet assay; colony forming assay; CHO/HGPRT test; ethylmethane sulfonate